ANALYSIS THE EFFECT USE DIGITAL PAYMENT ON PROBABILITY OF CONSUMPTION UNS STUDENTS - Fiqh, Yesskil Sufaha; Hakim, Lukman; Ignasiak-Szulc, Aranka (Journal of Applied Economics in Developing Countries, 2023)
This research is to find out whether there is a digital payment that the possibility of student consumption will be increasingly wasteful or become more efficient and choose to save money. The respondents of this study are active students of Universitas Sebelas Maret and have used digital payments in transactions. The number of samples taken in this study were 100 respondents. This research analysis technique uses quantitative methods using logistic regression. The results of this research are that the Income, Savings and Education variables do not have a significant influence on the possibility of consumption patterns in the use of digital payments. Meanwhile, the variables Expenditure, Age and Gender have a significant influence on the possibility of consumption patterns in using digital payments.